2017
DOI: 10.1016/j.nuclphysa.2017.05.097
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Perspective on Quarkonia from SPS via RHIC to LHC

Abstract: The objective of this paper is to assess the current theoretical understanding of the extensive set of quarkonium observables (for both charmonia and bottomonia) that have been attained in ultrarelativistic heavy-ion collisions over two orders of magnitude in center-of-mass energy. We briefly lay out and compare the currently employed theoretical frameworks and their underlying transport coefficients, and then analyze excitation functions of quarkonium yields to characterize the nature of the varying productio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…While for charmonium there are clear indications for the presence of a regeneration components in the observed yields [15], no such signals have been firmly established for bottomonium yet. One hint toward the onset of regeneration could be the small change in the bottomonium suppression when going from 2.76 to 5.02 TeV.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While for charmonium there are clear indications for the presence of a regeneration components in the observed yields [15], no such signals have been firmly established for bottomonium yet. One hint toward the onset of regeneration could be the small change in the bottomonium suppression when going from 2.76 to 5.02 TeV.…”
Section: Discussionmentioning
confidence: 91%
“…Measurements of charmonium yields e.g. have shown that for this lighter flavor indeed regeneration becomes quite important at LHC energies [15]. For bottomonium, only recently have there been studies carried out that include a regeneration component, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, we employ our previously developed semiclassical Boltzmann/rate equation approach which has been extensively tested by a wide variety of quarkonium observables from SPS via RHIC to LHC energies for both charmonia and bottomonia [27,[39][40][41]. Its results are largely consistent with other semi-classical approaches [28,30,[42][43][44][45][46][47], although quantitative cross comparisons under controlled conditions remain to be carried out [9]. Furthermore, the effects of explicit quantum evolution equations for quarkonia are receiving increased attention [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 93%
“…Quarkonium (bound heavy quark-antiquark states) are an intriguing probe of the quark-gluon plasma [1]. Originally proposed by Matsui and Satz [2], the suppression of quarkonia has remained an active topic of experimental [3][4][5][6][7][8] and theoretical [9][10][11][12][13][14][15] investigation ever since. The central idea is that a thermal medium tends to break up quarkonium bound states; one then investigates how strong this effect is expected to be theoretically, and how much such states are suppressed experimentally.…”
Section: Introductionmentioning
confidence: 99%